Penegakan Hukum Oleh Kepolisian Resor Tanjung Jabung Barat terhadap Pelaku Tindak Pidana Penadahan - Retno Kusumawardani Wardani; Setly Selva Yuneida (Universitas Batanghari Jambi, 2022)
Nowadays, there are many criminal acts committed by humans to achieve the desired goals, including committing criminal acts of holding goods resulting from criminal acts. The research method used in this study is empirical juridical so that it examines first related to the occurrence of criminal acts of detention in Tanjung Jabung Barat, then linked to the legal rules regarding detention, namely Article 480 of the Criminal Code (KUHP) is descriptive and the source is library research (liberty research) and field research (field research). In this study, the approach used is socio-legal research and the data analysis is qualitative analysis. The results of this study explain that law enforcement by the Tanjung Jabung Barat Resort Police against perpetrators of criminal acts of detention is not maximally carried out in accordance with the provisions/procedures of law enforcement officers, both at the level of investigation, prosecution and at the level of court judge decisions. Because it involves actors with a well-organized network. The obstacle faced is the provisions of Article 12 paragraph (2) of the Criminal Code which only regulates the general maximum law and the general minimum law which causes the judge's decision to be weak (depending on the judge only) so that the possibility of a sense of deterrence for the perpetrators of detention is very far away and due to factors it is difficult to find and identify places of detention, the detention is carried out because it has a hidden or hidden network and has a very neat cooperation, making it difficult to uncover and trace it and the efforts made to overcome the obstacles are to take strict action by law who is proven to have held detention, by seek to provide a more severe punishment, conduct raids in places/shops suspected of buying stolen goods, pawnshops and so on, approaches through religion, counseling in the field of law and so on.